GE_GERICHTE C/19460/2017 vom 29. Januar 2019 - GE Cour de justice (2019)
DIVORCE ; OBLIGATION D'ENTRETIEN ; PRÉVOYANCE PROFESSIONNELLE ; BONIFICATION POUR TÂCHES ÉDUCATIVES | CC.285; CC.122; CC.124.letb; CPC.281